2016
DOI: 10.1158/1078-0432.ccr-16-0135
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Human Breast Milk Promote EMT

Abstract: TGFβ2 is significantly upregulated in breast milk exosomes during weaning/early involution. Breast milk exosomes containing high levels of TGFβ2 induce changes in both benign and malignant breast epithelial cells, consistent with the development and progression of breast cancer, suggesting a role for high TGFβ2-expressing breast milk exosomes in influencing breast cancer risk. Clin Cancer Res; 22(17); 4517-24. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 30 publications
3
94
0
Order By: Relevance
“…According to more than 30 studies, from different teams around the world, milk EVs resisted in vitro digestion (Benmoussa et al., ; Kahn et al., ; Liao et al., ; Rani et al., ; Shandilya et al., ; Vashisht et al., ) were internalized by recipient cells upon co‐incubation (Admyre et al., , 2008; Aqil et al., , ; Badawy et al., ; Golan‐Gerstl et al., ; Hock et al., ; Kahn et al., ; Liao et al., ; Maburutse, Park, Oh, & Kim, ; Martin et al., ; Matsuda & Patel, ; Mobley et al., ; Munagala et al., ; Naslund et al., ; Qin et al., ; Vashisht, Rani, Onteru, & Singh, ; Yu et al., ), transduced through the intestinal wall in vitro (Rani et al., ; Shandilya et al., ; Wolf et al., ), and were detected in animal models after ingestion (Manca et al., ; Munagala et al., ) or intravenous injection (Somiya, Yoshioka, & Ochiya, ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…According to more than 30 studies, from different teams around the world, milk EVs resisted in vitro digestion (Benmoussa et al., ; Kahn et al., ; Liao et al., ; Rani et al., ; Shandilya et al., ; Vashisht et al., ) were internalized by recipient cells upon co‐incubation (Admyre et al., , 2008; Aqil et al., , ; Badawy et al., ; Golan‐Gerstl et al., ; Hock et al., ; Kahn et al., ; Liao et al., ; Maburutse, Park, Oh, & Kim, ; Martin et al., ; Matsuda & Patel, ; Mobley et al., ; Munagala et al., ; Naslund et al., ; Qin et al., ; Vashisht, Rani, Onteru, & Singh, ; Yu et al., ), transduced through the intestinal wall in vitro (Rani et al., ; Shandilya et al., ; Wolf et al., ), and were detected in animal models after ingestion (Manca et al., ; Munagala et al., ) or intravenous injection (Somiya, Yoshioka, & Ochiya, ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Twenty‐one studies involving milk EVs from humans, rat, camels, and most often cow milks reported milk EVs bioactivity in vitro on cells (Admyre et al., ; Aqil et al., , ; Badawy et al., ; Golan‐Gerstl et al., ; Hock et al., ; Martin et al., ; Matsuda & Patel, ; Mobley et al., ; Munagala et al., ; Naslund et al., ; Qin et al., ; Vashisht et al., ; Yu et al., ) and in vivo in animal models (Agrawal et al., ; Aqil et al., , ; Badawy et al., ; Leiferman et al., ; Munagala et al., ; Munagala et al., ; Somiya et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Reduced CK8 expression is regarded as an indicator of EMT, leading to more malignant forms of cancer [89]. Breast milk exosomes containing high levels of TGF-β2 can induce changes in both benign and malignant breast epithelial cells, consistent with the development and progression of breast cancer, which occurs due to alterations in cellular shape and the actin cytoskeleton and the loss of cell-cell junctions [90]. TGF-β-induced EMT was found to restrain cell invasion, which may be alleviated by the overexpression of hyperactivated Ras [91].…”
Section: The Role Of the Cellular Cytoskeleton In Epithelial-mesenchymentioning
confidence: 99%